Learning from pandemic precarity: The future of early career researchers in qualitative health research - Madeleine Tremblett; Tom Douglass; Jack Joyce; Alistair Anderson; Natalie Flint; Tanisha Spratt (Elsevier, 2023)
This commentary is a critical reflection by early career researchers (ECRs) working in qualitative health research (QHR) during the COVID-19 pandemic. The consequences of the pandemic have been acutely felt by ECRs working in QHR. Many studies stopped, almost overnight, as healthcare institutions restricted access and redeployed staff, forcing researchers to redesign or even abandon projects. We reflect on the burden of these challenges for insecurely employed QHR ECRs and discuss the approaches adopted to retain scientific integrity and redesign studies. We also highlight the impact of COVID-19 on career development and relationship building - both during the emergency pandemic period and in the reshaped context of academia that continues to operate under the long shadow of COVID-19. We conclude by outlining a programme of change for how the practice and organisation of QHR could be reshaped, identifying opportunities for learning from the pandemic. Embracing these learnings will benefit not only the careers and wellbeing of QHR ECRs, but also universities, funders and the overall health and future of QHR.